Effect of Leakage Delay on Stability of Neutral-Type Genetic Regulatory Networks - Li Li; Yongqing Yang; Chuanzhi Bai (Abstract and Applied Analysis)
The stability of neutral-type genetic regulatory networks with leakage delays is considered. Firstly, we describe the model of genetic regulatory network with neutral delays and leakage delays. Then some sufficient conditions are derived to ensure the asymptotic stability of the genetic regulatory network by the Lyapunov functional method. Further, the effect of leakage delay on stability is discussed. Finally, a numerical example is given to show the effectiveness of the results.